Digestive alkaline proteinases from Serranus scriba viscera: Characteristics, application in the extraction of carotenoproteins from shrimp waste, and evaluation in laundry commercial detergents. Issue 3 (July 2015) - Nasri, Rim; Abed, Hajer; Karra-châabouni, Maha; Nasri, Moncef; Bougatef, Ali
Abstract: In this study, alkaline proteases from the viscera of the Serranus scriba were extracted and characterized. Interestingly, the crude alkaline protease showed optimum activity at pH 11.0. The relative activities at pH 10.0 and 12.0 were about 79% and 80.5% of that at pH 11.0, respectively. In addition, the crude protease was stable over a broad pH range (7.0–12.0) retaining more than 80% of its initial activity after incubation for 1 h at 25 °C. The optimum temperature for the crude enzyme activity was 50 °C. The crude alkaline protease extract showed high stability towards various surfactants and bleach agents. In addition, the crude enzyme showed high stability and compatibility with various solid and liquid commercial detergents. Further, proteases from S. scriba viscera were found to be effective in the extraction of carotenoproteins from shrimp waste. Extracted carotenoproteins were found to exhibit antioxidant activity evaluated through DPPH radical scavenging activity and inhibition of β-carotene bleaching assay. These results suggest that proteases from S. scriba viscera could be used as additive in laundry detergents and in the deproteinisation of shrimp wastes to extract carotenoproteins.